Do young and older adult populations perform equivalently across different automatic face-trait judgements? Evidence for differential impacts of ageing - Chithra Kannan; Alex L. Jones; John Towler; Jeremy J. Tree (PLoS ONE, 2025)
Accurate implicit personality trait judgements can be made from faces, but as yet the focus has been on young participants making judgements of young faces. The current study sought to explore if similar patterns of performance are seen across the age range, with both young and older adult groups. In addition, we investigated whether implicit trait judgements are associated with cognitive, and trait factors including face recognition, emotional expression perception, autism traits, and alexithymia traits. Across two experiments we explored the extent to which young and older adult populations were able to make accurate implicit associations from faces signalling two different traits – extraversion (positive) and neuroticism (negative). Interestingly, we find that young participants were accurate at making both kinds of automatic trait judgments, and older adults were equivalent to younger controls for the neuroticism personality trait but impaired with automatic extraversion judgements. In both studies, implicit associations were unrelated to any of the other cognitive and trait factors we measured. Based on this pattern of findings, we conclude that face-based implicit trait judgements utilise some independent processes to other face processing abilities, and that the interpretation of particular personality traits is differentially impacted by the ageing process.